The influence of the project-based learning model assisted by audiovisual media on students’ ability to write procedure texts at SMP - Siregar, Elfriati; Telaumbanua, Sadieli; Perangin-angin, Esra (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
A well-prepared abstract enables the reader to identify the basic content of a document quickly and accurately. This study examines the effect of Project Based Learning model assisted by audiovisual media on students' ability to write procedural texts at SMP Negeri 2 Simpang Kiri, Subulussalam City. Using a quasi-experimental design with post-test only control group, the research involved 53 seventh grade students divided into experimental and control groups. Results showed significant improvement in the experimental group (average score 81.73) compared to the control group (average score 64.56), with t-test results of 8.337 > 1.671. Student perceptions indicated positive responses to this learning model despite some technical challenges. The findings suggest that integrating project-based learning with audiovisual media effectively enhances procedural text writing skills.